Evaluating The CLT-Ness Of Bahasa Inggris Untuk SMA/ MA/SMK/MAK Kelas X Semester 1 Coursebook For Secondary School Students In Indonesia - Puput Arfiandhani (Universitas Muhammadiyah Yogyakarta, 2016)
Materials and methodology play a significant role in a language classroom. These two elements need to be in line with each other to help achieve the shared learning goals. One of the method- ologies that have been widely employed, but still not well-permeated among teachers in Indonesia is Communicative Language Teaching (CLT). However, not many studies on seeing the relationship between methodology and materials have been conducted. To bridge this gap, this study aims to evaluate the CLT-ness of the national course book Bahasa Inggris untuk SMA/MA/SMK/MAK Kelas X Semester 1. To conduct the evaluation, a checklist adapted from Grant’s and Cunningsworth’s was employed as an evaluation tool. The research findings indicate that while the coursebook made a clear attempt to uphold CLT, as observed from its learning goals for each chapter and the coursebook introduction, several aspects of the coursebook, such as the tasks and activities, needed to be improved.